Digitalization of Islamic Education: Challenges to The Spirit of Humanistic and Transcendental Learning - Manasik, Jauhari; Kholis, Nur; Fatoni, Imam; Hasan, Sholikin (Al'ulum Jurnal Pendidikan Islam, 2026)
This research aims to analyze the challenges of digitalization to the spirit of humanistic and transcendental learning in Islamic educational institutions. Using a descriptive qualitative approach with the type of literature study and field observation, this study collects data from various reputable scientific literature as well as information from Islamic education practitioners as key informants. The analysis was carried out through content analysis techniques to dissect the phenomenon of cyber interaction in the context of tarbiyah. The results of the study show that digitalization triggers the mechanization of learning which reduces the role of teachers from murabbi figures (soul guides) to mere technical facilitators. Screen-mediated interactions create a "digital alienation" that organically inhibits the internalization of human manners and empathy. Furthermore, the cognitive-quantitative dominant digital evaluation system tends to ignore the inner transformation and transcendental awareness of students as servants of God.